The effects of undocumented immigration on the employment opportunities of low skill natives in the United States - Schultz, Russell W., author; Shields, Martin, advisor; Weiler, Stephan, advisor; Pena, Anita, committee member; Davies, Stephen, committee member (Colorado State University. Libraries, 2012)
The economic effects of immigration have been well studied, but the majority of this research has not attempted to isolate the effects of undocumented immigration. Isolating this effect is a difficult task because dearth amounts of data exist for these individuals. This paper provides a substantial contribution to the economic impact of immigration for two reasons. First, it emulates a methodology adopted by notable immigrant demographers to generate annual state level estimates of the undocumented population between 1994 and 2010 in the United States. These estimates alone are very important to this topic because no other entity has attempted to accomplish this task. Secondly, this paper incorporates these estimates into a fixed effect dynamic model to capture the economic impact of undocumented immigrants on low skill native labor force participation rates (LFPR) and unemployment rates across the United States between 1994 and 2009. Overall, undocumented immigrants have a menial impact on the native low skill LFPR and do not affect low skill unemployment rates. Additionally, the methods used in this paper allow us to isolate the effects of documented immigrants on the same native low skill employment indicators. The results suggest that documented immigrants do not have a statistically significant effect to either low skill employment indicator, which is also an important conclusion.
Keywords: economic; effect; employment; immigration; native; undocumented